Relationship Between Affective Temperaments and Suicide Risk in Patients With First-Onset Major Depressive Disorder - Yin, Lu; Song, Tian-He; Wei, Yan-Yan; Zhang, Li-Gang; Zhou, Shuang-Jiang; Yu, Jian-Jin; Zhang, Li-Ye; Li, Hong-Juan; Chen, Jing-Xu (Frontiers in Psychiatry, 2022)
Background: People may endorse suicidal behavior during a major depressive episode. Affective temperaments may play a role in this risk. We explored the relationship between affective temperaments and suicide and identified some traits that can predict suicide risk in depression. Methods: We analyzed the results of Temperament Evaluation of the Memphis, Pisa, Paris, and San Diego Auto-questionnaire (TEMPS-A) in 284 participants recruited from a psychiatric clinic and the community in Beijing and compared the subscale scores (cyclothymic, dysthymic, anxious, irritable and hyperthymic) among major depressive disorder (MDD) versus the general population as well as depressive patients with versus without suicide risk, using student’s test, Chi-square test, rank sum test, and multivariable regression modeling. Results: The incidence of suicidal risk in depressive subjects was 47.62% (80/168). Being unmarried (P<0.001), unemployment (P=0.007) and temperaments of dysthymic, cyclothymic, anxious, and irritable scores (all P<0.001) were significantly more prevalent in depressive patients than in the general population. A young age (P<0.001), female sex (P=0.037), being unmarried (P=0.001), more severe depression (P<0.001), and dysthymic, anxious and cyclothymic temperament (all P<0.05) were significantly more prevalent in depressive disorder patients with than without suicide risk. The logistic regression analysis showed that younger age (OR=0.937, 95% CI 0.905~0.970), female sex (OR=2.606, 95% CI 1.142~5.948), more severe depression (OR=1.145, 95% CI 1.063~1.234), cyclothymic temperament (OR=1.275, 95% CI 1.102~1.475) and dysthymic temperament (OR=1.265, 95% CI 1.037~1.542) were all independently associated with high suicidal risk in first-onset major depressive patients (P<0.05). Conclusion: Temperament traits differ between the general population and people suffering from major depressive disorder. Major depressive disorder subjects with much more severe depressive symptoms and cyclothymic or dysthymic temperament were at high risk of suicide.